Barriers and prospects for skin grafting in burn treatment across African countries - Bbaale, Dorothy; Mohr, Christoph; Lindert, Judith; Allorto, Nikki; Mabanza, Tresor; Katabogama, Jean Bosco; Chamania, Shobha; Elrod, Richard; Boettcher, Michael; Elrod, Julia (Burns, 2024)
Introduction - The current standard management of full-thickness or deep dermal burns is early tangential excision and skin grafting. A conservative approach to deep burns without the option of skin grafting results in delayed wound healing, possibly leading to wound infection and is associated with hypertrophic scarring and increased morbidity and mortality. The aim of this study was to improve the understanding of the management and availability to perform skin grafting for burns on the African continent. It also sought to identify challenges and perceived improvements. - Methods - A web-based, structured, closed-formatted, multinational survey was designed to gather information on the current state and availability of skin grafting of burn wounds on the African continent. The questionnaire consisted of 27 questions, available in English and French. It was reviewed within the GAP-Burn collaboration network and sent to 271 health care professionals who had participated in a previous study and had initially been recruited by means of the snowball system. - Results - The questionnaire was completed 84 times (response rate: 31.0%), of which 3 were excluded. Responses originated from 22 African countries. The majority 71 (87.7%) resulted from countries with a low Human Development Index (HDI), 7 (8.6%) from medium HDI countries. Split thickness skin grafting (STSG) is performed in 51 (63.0%) centers. The majority considers STSG to reduce length of stay (72.8%) and improve scarring (54.3%), yet some indicated that STSG is associated with increased risk of donor site infection (8.6%) and severe bleeding (7.4%). Factors preventing increased grafting included lack of equipment and training. - Conclusion - Skin grafting is not performed in a significant number of hospitals treating burns. The majority of the staff believe that more skin grafting would lead to a better outcome. Advocacy and improved infrastructure, human resources coupled with introduction to well-structured health coverage for all in African countries could help to better access and affordability in burn care.